2006
DOI: 10.1177/1534734606294538
|View full text |Cite
|
Sign up to set email alerts
|

An Assessment of the Disease Burden of Foot Ulcers in Patients With Diabetes Mellitus Attending a Teaching Hospital in Lagos, Nigeria

Abstract: The major part of the burden of people with diabetes mellitus (DM) is their impaired quantity and quality of life. This is due to acute and chronic complications of which diabetic foot ulceration (DFU) takes the greatest toll. Most studies on the disease burden of DFU were carried out in developed countries, and to date, no indigenous study has addressed the burden of foot ulceration in Nigerians with DM. This study attempted to determine the disease burden of this important DM complication. The study was carr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
60
3

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(73 citation statements)
references
References 9 publications
10
60
3
Order By: Relevance
“…Also a review of studies from these developing countries show variation in the cost spent on managing diabetic foot with no homogeneity unlike what was obtained in developed nations [19]. The cost obtained from this study was however higher than what was found in a similar study done in Lagos, Southwestern Nigeria in 2006 where the total cost of illness of diabetic foot ulcer was estimated at 180,581.60 Nigerian naira or $1003.26 [20]. The higher cost from our study could be attributed to inflation that has being rising over the years and it could also be attributed to improvement in the health care system with use of high tech machines for diagnosis and treatment which will cost more.…”
Section: Discussioncontrasting
confidence: 54%
See 1 more Smart Citation
“…Also a review of studies from these developing countries show variation in the cost spent on managing diabetic foot with no homogeneity unlike what was obtained in developed nations [19]. The cost obtained from this study was however higher than what was found in a similar study done in Lagos, Southwestern Nigeria in 2006 where the total cost of illness of diabetic foot ulcer was estimated at 180,581.60 Nigerian naira or $1003.26 [20]. The higher cost from our study could be attributed to inflation that has being rising over the years and it could also be attributed to improvement in the health care system with use of high tech machines for diagnosis and treatment which will cost more.…”
Section: Discussioncontrasting
confidence: 54%
“…The estimated cost from our study is much lower than what was found in advanced countries like the United States. Holzer et al in 1998 estimated the [20]. Harrington in 2000 from his study also found that 73.7% of the total cost of illness was attributable to direct cost of illness [23].…”
Section: Discussionmentioning
confidence: 99%
“…This due to the fact, that these variables are present in high levels in non-diabetic ulcer foot group. Several studies have shown association between diabetic foot and hypertension, albuminuria, retinopathy, neuropathy, HbA1c, cholesterol, HDL, LDL and triglyceride (8,(11)(12)(13)(14)(15)(16). Peripheral vascular disease is another important contributor in pathogenesis of diabetic foot, and prevalence of peripheral vascular disease in Sudan in 1989 was estimated to be 6.2% and this increased to 10% in 1995 (18,20).…”
Section: Discussionmentioning
confidence: 99%
“…Increase in prevalence of diabetes complications in Africa was attributed to rise in financial health expenditure, poor medical facility and lack of adequate diabetes service in urban and rural areas (9,10). The prevalence of diabetic foot in Cameroon, Nigeria and Tanzania were estimated to be 13%, 9.5% and 15% respectively (11)(12)(13). The cost associated with diabetic foot is enormous.…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of diabetic foot ulcer (DFU) ranged between 1.0% and 4.1% in the United States (US), 4.6% in Kenya, and 20.4% in Netherlands. 5,6,7 Hospital-based studies demonstrated that the prevalence of limb ulceration were between 11.7% and 19.1% among individuals with diabetes in Nigeria. 8,9 The prevalence of DFU among hospitalized patients with diabetes in Iran was 20%.…”
Section: Introductionmentioning
confidence: 99%